DisKo: playful tool to encourage collaborative work for college students in 2021 - Cassinelli Doig, Adriana (2022)
This article documents a qualitative and quantitative investigation, which has included the application of Disko, a ludic tool composed by five mini games for virtual classes. The orientation of design towards a people-centered vision is considered relevant by the authors, to achieve this, the empowerment of empathy is decisive. Cooperation dimension was prioritized from five indicators: collaborative work, leadership, interaction, assertive communication and commitment. The sample included 94 students from two subjects, active in first and second cycles during 2021-I. The applied design was quasi-experimental with posttest; with a control group (CG) that diagnosed usual tools, and an experimental group (EG), to which DisKo was applied. This tool proved to be useful after being statistically tested. It collaborated in empathic learning increase between students and contributed in social satisfaction improvement, making teacher work easier.